The Cognitive Significance of Language Proficiency Zeal (Eurasian Journal of Learning and Academic Teaching, 2023)
One of the interpretations is a cognitive ability a person, which is realized at different levels of the language system, associated with the formation and expression of certain knowledge about the world. This knowledge underlies human cognitive activity, which focused on establishing the cognitive significance of language proficiency zeal, its information content. In a broad sense, cognitive activity is an activity as a result of which a person comes to a specific decision and knowledge, i.e. thinking agent ness, leading to understanding (interpretation) of something